Comparison of Stone Dusting Efficiency When Using Different Energy Settings of Holmium: YAG Laser for Flexible Ureteroscopic Lithotripsy in The Treatment of Upper Urinary Tract Calculi - Chen, Shulian; Fu, Ni; Cui, Wei; Zhao, Zeju; Luo, Xu (Urology Journal, 2020)
Purpose: The aim of this study is to evaluate the impact of different pulse energy settings on dusting efficiency in flexible ureteroscopic lithotripsy (fURSL) for the treatment of upper urinary tract calculi. Materials and Methods: Data of 88 consecutive patients who underwent fURSL for upper urinary tract calculi by a single surgeon in our department from August 2017 to August 2018 were reviewed retrospectively. Lumenis Power Suite 100W lithotripter with a 200 ?m laser fiber was used to comminute stones. According to energy settings, patients were divided into three groups- low energy group (LE: 0.3-0.6J), middle energy group (ME: 0.7-1.0J), high energy group (HE: 1.1-1.5J). Frequency was set at 30Hz in all patients. ANOVA and Chi square tests were applied to compare the difference of the mean lithotripsy and operation time, early stone-free rate (eSFR), overall stone-free rate (oSFR) and complication rate. Results: A total of 32, 36 and 20 patients were included in the LE, ME and HE groups, respectively. There was no difference in the age, gender distribution or in any other stone characteristics among the three groups. The mean lithotripsy time of LE, ME, HE was 10.9 ± 7.6, 16.1 ± 7.0, 23.0 ± 15.0 min respectively. The mean operation time of the three groups was 16.9 ± 7.7, 22.3±7.1, 29.2±14.9 min respectively. There were significant differences on the mean lithotripsy time (P = 0.002) and the mean operation time (P = 0.001) among the three groups. The stone-free rate was 31.8% and 87.5% respectively in eSFR and oSFR. No statistical significance was detected among the three groups in terms of the eSFR (P = 0.89), oSFR (P = 0.86), and complication rate (P = 0.97). Conclusion: In fURSL with dusting, low energy (0.3-0.6J) is more efficient than middle (0.7-1.0J) and high energy (1.1-1.5J). As energy increased, dusting efficiency decreased dramatically. Consequently, we recommend low pulse energy (0.3-0.6J) as the optimal dusting strategy for fURSL.